Analysis Of Low Self-Efficacy Among Students Using Creative Problem-Solving Techniques - Ai Solihah; Siti Julaeha; Muh. Aripin Nurmantoro (Badan Penerbit STIEPARI Press, 2024)
Self-efficacy of students in understanding educational statistics material is the main focus of this analysis. Through the Finding Facts stage, the complexity of the material, lack of support from lecturers, and ineffective curriculum/methods of teaching are identified as key factors influencing the low self-efficacy of students. The Finding Acceptance stage confirms a high acceptance of these findings as issues needing to be addressed. The implications of this analysis emphasize the need for holistic action to enhance student self-efficacy, through simplifying materials, increasing lecturer support, and revolutionizing curriculum and teaching methods. Thus, the article proposes concrete steps to create a supportive and empowering learning environment for students facing challenges in learning educational statistics.